Survival Chances of Start-Ups - do Regional Conditions Matter? - Oliver Falck (European Regional Science Association (ERSA), 2005)
This paper analyses the effect of industry, regional and firm level characteristics on the post entry performance of newly founded businesses by means of an econometric survival time model. First preference is given to an accelerated failure time model assuming a log-logistic distribution. The dataset involves a representative sample of establishments in the private sector provided by the Institute for Employment Research (IAB). The data relates to West German states during 1993-2002 period. A start-up's The likelihood of failure tends to be relatively high in industries characterized by a high minimum efficient size and high numbers of entries. The regional dimension has a considerable impact upon improvements of estimation results. On the firm level, the size of the firm seems to be the best predictor for the likelihood of failure.
Keywords: 330